The Mental Burden of Parents of Children with Thalassemia - Gita Septyana; Ai Mardhiyah; Efri Widianti (Jurnal Keperawatan Padjadjaran, 2019)
Thalassemia is an inherited blood disorder in which there is a chronic abnormality of red blood cells. When a child suffers from a severe illness, the family usually acts as caregivers, which put them at risk of experiencing a burden of care. This study aims to identify the level of charge perceived by parents caregivers of children with thalassemia. A quantitative approach was used in this research to obtain data by using a continuous sampling. The samples in this research consisted of 71 parents of children with thalassemia, who are either their biological father or mother who attended thalassemia center on August 30, 2017 - September 13, 2017. The instrument was used in this research was modified from a Caregiver Burden Scale instrument (developed by Elmstahl). The data obtained were analyzed using a descriptive statistical technique in which parents burden is categorized into three levels: mild, moderate, and severe levels of burden, and they are measured in percentage. The result showed that 36 respondents (50.7%) perceived a mild level of burden, 31 respondents (43.7%) perceived moderate level of burden, and four respondents (5.6%) saw the severe level of burden. This study concludes that most respondents perceived a mild and moderate level of burden, but in terms of responsibility, economy, expectation, and anxiety, they showed a severe degree of burden. Nurses are suggested to maintain or alleviate the burden by providing education, counseling, emotional support and adaptive coping mechanisms for parents of children with thalassemia.